A new Gammarus species (Crustacea, Amphipoda, Gammaridae) from Northwestern Islands, South Korea - Kwon, So-Yeon; Kim, Min-Seop; Heo, Jun-Haeng; Kim, Young-Hyo (Zootaxa, 2020)
A new species, Gammarus baengnyeongensis sp. nov., belonging to the family Gammaridae Leach, 1814 was collected from the Baengnyeongdo and Daecheongdo islands in South Korea. This new species is characterized by the flagellum of antenna 2 with calceoli, and the length ratio of outer ramus to inner ramus of uropod 3. Descriptions of diagnostic characteristics of the species are provided in the text. We performed statistical analysis to confirm the significance of morphological differences of interspecies. Additionally, we compare the new species to related species by the partial sequence of the mitochondrial cytochrome c oxidase subunit 1 (CO1) gene. Genetic distances between the new species and closely related species rated from 29.1–40.8%, which highly supports Gammarus baengnyeongensis sp. nov. as a valid species. In this study, we add one new Gammarus species in Korean waters.